The New Development Economics: We Shall Experiment, but How Shall We L earn? - Rodrik, Dani (SSRN, 2008)
Development economics is split between macro-development economists - who focus on economic growth, international trade, and fiscal/macro po licies - and micro-development economists - who study microfinance, ed ucation, health, and other social programs. Recently there has been su bstantial convergence in the policy mindset exhibited by micro evaluat ion enthusiasts, on the one hand, and growth diagnosticians, on the ot her. At the same time, the randomized evaluation revolution has led to an accentuation of the methodological divergence between the two camp s. Overcoming the split requires changes on both sides. Macrodevelopme nt economists need to recognize the distinct advantages of the experim ental approach and adopt the policy mindset of the randomized evaluati on enthusiasts. Micro-development economists, for their part, have to recognize that the utility of randomized evaluations is restricted by the narrow and limited scope of their application. As the Chinese exam ple illustrates, extending the experimental mindset to the domain of e conomy-wide reforms is not just possible, it has already been practice d with resounding success in the most important development experience of our generation.
Keywords: Economics; Finance; Health Care; International Development; International Economics; International Trade; Macroeconomics; Microeconomics; Social Policy; Welfare